2009
DOI: 10.1002/humu.21055
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in theGUCA1Agene involved in hereditary cone dystrophies impair calcium-mediated regulation of guanylate cyclase

Abstract: ABSTRACT:The GUCA1A gene encodes the guanylate cyclase activating protein 1 (GCAP1) of mammalian rod and cone photoreceptor cells, which is involved in the Ca 2+ -dependent negative feedback regulation of membrane bound guanylate cyclases in the retina. Mutations in the GUCA1A gene have been associated with different forms of cone dystrophies leading to impaired cone vision and retinal degeneration. Here we report the identification of three novel and one previously detected GUCA1A mutations: c.265G>A (p.Glu89… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
90
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(93 citation statements)
references
References 34 publications
(35 reference statements)
2
90
1
Order By: Relevance
“…1B). This was consistent with earlier observations that the region downstream from Arg-182 tolerates replacement with the C terminus from recoverin (32). However, we also found that, contrary to earlier expectations based on the substitution of larger fragments in GCAP primary structure (32,47), none of the individually tested surface residues in the exiting helix of EF-hand 4 or in ␣-helices 10 and 11 was essential for the cyclase activation.…”
Section: Mutagenesis and The Primary Screening For The Residues Affecsupporting
confidence: 92%
See 3 more Smart Citations
“…1B). This was consistent with earlier observations that the region downstream from Arg-182 tolerates replacement with the C terminus from recoverin (32). However, we also found that, contrary to earlier expectations based on the substitution of larger fragments in GCAP primary structure (32,47), none of the individually tested surface residues in the exiting helix of EF-hand 4 or in ␣-helices 10 and 11 was essential for the cyclase activation.…”
Section: Mutagenesis and The Primary Screening For The Residues Affecsupporting
confidence: 92%
“…The binding patch in GCAP1 extends from the EF-2 loop to the exiting helix ␣5 of EF-hand 2 and the entering helix ␣6 of EF-3. The hinge region between the two semi-globules in the GCAPs has been implicated in cyclase regulation (32,47). We found that three non-charged residues exposed on the surface of exiting helix ␣5 of EF-2 (Met-74, Val-77, and Ala-78) participate in the cyclase binding.…”
Section: Target-binding Interface On Gcap1mentioning
confidence: 83%
See 2 more Smart Citations
“…The mOrangeRetGC1VenusN chi- Fig. 2; the a max values for stimulation by GCAPs in the absence or presence of 1 and 2 M M26R GCAP1 only slightly change for stimulation by GCAP1 (27,26, and 25 nmol of cGMP/min/mg, respectively) or GCAP2 (22,21, and 19 nmol of cGMP/min/mg, respectively), but the K 1/2GCAP increased in the presence of M26R GCAP1 for wild type GCAP1 (1.5, 4, and 6.7 M, respectively) and GCAP2 (1.7, 4.7, and 7.4 M, respectively). The Hill coefficient increased for GCAP1 (from 1.17 in the absence to 1.53 in the presence of 2 M M26R GCAP1) and for GCAP2 (from 1.14 in the absence to 1.54 in the presence of 2 M M26R GCAP1).…”
Section: Gcap1 and Gcap2 Compete For Binding To The Same Retgc1mentioning
confidence: 94%